If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2 + 2x) = 4(3 + -3x) (2 * 5 + 2x * 5) = 4(3 + -3x) (10 + 10x) = 4(3 + -3x) 10 + 10x = (3 * 4 + -3x * 4) 10 + 10x = (12 + -12x) Solving 10 + 10x = 12 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 10 + 10x + 12x = 12 + -12x + 12x Combine like terms: 10x + 12x = 22x 10 + 22x = 12 + -12x + 12x Combine like terms: -12x + 12x = 0 10 + 22x = 12 + 0 10 + 22x = 12 Add '-10' to each side of the equation. 10 + -10 + 22x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 22x = 12 + -10 22x = 12 + -10 Combine like terms: 12 + -10 = 2 22x = 2 Divide each side by '22'. x = 0.09090909091 Simplifying x = 0.09090909091
| (4n-7)(8n-7)= | | 17=1+4p | | cos(3x+20)=0.2 | | 240=12x | | ab=9 | | 1=4+p | | 8x^2-12y+4=y+10 | | cos(3o+20)=0.2 | | 4+3x+6=4x-5 | | x+(-10)=-22 | | 27-7r=-(1+3r) | | 20+2p=8+6(-8+2p) | | -5(a+6)=-14-7a | | 2y^2+14=104 | | x(5)=-5-1 | | 2(x+6)=3(x+4)+5 | | 180(n-1)=900 | | -84=7(p-4) | | -105=-7(1-2r) | | -75-18v=-70 | | =9p^5q+6p^4-15p^2q^4 | | -84=6(n-7) | | 2sinxta*n*x-3=0 | | ln(1-x)=2 | | 8m-21=51 | | 8x+8=4-x | | -3n+2=20 | | 2z+5=5z-4z | | -24=3m | | 3.4x+7=10 | | -17+v=-19 | | 19=n+8 |